Potential of DGT in a new fractionation approach for studying trace metal element impact on anaerobic digestion: the example of cadmium. (April 2017) - Bourven, I.; Casellas, M.; Buzier, R.; Lesieur, J.; Lenain, J.-F.; Faix, A.; Bressolier, P.; Maftah, C.; Guibaud, G.
Abstract: Cadmium impact during anaerobic digestion (AD) of lactoserum was investigated by DGT (Diffusive Gradients in Thin films) considering not only total trace metallic element (TME) concentration, but also three operational fractions: particulate, inert soluble and available. During the lactoserum AD process, the effect of addition of different Cd concentrations (1; 5 and 10 μg l −1 ) was investigated in Biomethane Potential (BMP). Volume of biogas produced, % genetic dissimilarity and different enzymatic activities (TTC-dehydrogenase, β-galactosidase and cofactor F420 content) were followed as biological markers during AD of lactoserum. This study demonstrated that inert soluble and DGT-available fractions of Cd impacted the biological tags at the beginning of AD while the Cd particulate fraction had the highest impact later in AD. Graphical abstract: Highlights: A Cd fractionation method is proposed as a bioreactor of anaerobic digestion. Cd fractionation consists of particulate, soluble and available Cd using DGT. At t = 0d, Cd soluble and available fractions seem responsible for the negative effect on AD. At t = 21d, Cd particulate fraction seems responsible for the negative effect on AD.